2017
DOI: 10.1002/app.45469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymer swelling and dissolution into food simulants on the release of graphene nanoplates and carbon nanotubes from poly(lactic) acid and polypropylene composite films

Abstract: The study compared the effects of swelling and dissolution of a matrix polymer by food simulants on the release of graphene nanoplates (GNPs) and multiwall carbon nanotubes (MWCNTs) from poly(lactic) acid (PLA) and polypropylene (PP) composite films. The total migration was determined gravimetrically in the ethanol and acetic acid food simulants at different time and temperature conditions, while migrants were detected by laser diffraction analysis and transmission electron microscopy. Swelling, thermal analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Thermal conductivity and diffusivity of GNP nanocomposites were improved by the addition of graphene nanoplatelets by 181% and 214%, respectively. Thermal transport in obtained PLA/GNP composites is a thriving area of research thanks to graphene's extraordinary heat conductivity properties and its In our previous studies [50][51][52] it was found that the PLA is still biodegradable and, only if there is a burning of composites (T < 850 • C), residual ash contains an amount of graphite and carbon nanotubes, creating concerns about environmental pollution and damage. A quantitative and qualitative risk assessment has been carried out in two cases-so-called "bad practices" (not in compliance with safety measures) and "good practices" (subject to modern safety measures).…”
Section: Discussionmentioning
confidence: 99%
“…Thermal conductivity and diffusivity of GNP nanocomposites were improved by the addition of graphene nanoplatelets by 181% and 214%, respectively. Thermal transport in obtained PLA/GNP composites is a thriving area of research thanks to graphene's extraordinary heat conductivity properties and its In our previous studies [50][51][52] it was found that the PLA is still biodegradable and, only if there is a burning of composites (T < 850 • C), residual ash contains an amount of graphite and carbon nanotubes, creating concerns about environmental pollution and damage. A quantitative and qualitative risk assessment has been carried out in two cases-so-called "bad practices" (not in compliance with safety measures) and "good practices" (subject to modern safety measures).…”
Section: Discussionmentioning
confidence: 99%
“…The overall migration rate and migration rate of nanofillers are studied widely for packaging materials based on petro-based nanocomposites such as low density polyethylene (LDPE) nanocomposites with different types of nanofillers like nanosilver (Hannon et al, 2016), nanocarbon black (Bott et al, 2014b), nanoclays (Echegoyen et al, 2016), and nanotitanium nitride (Bott et al, 2014a). PLA nanocomposites are also of a particular concern in migration studies of bionanocomposite systems reinforced with different nanofillers such as sliver-based modified MMT nanoclays (Busolo et al, 2010), Cloisite nanoclays (Schmidt et al, 2009), CNCs (Fortunati et al, 2012), multiwalled CNTs (Velichkova et al, 2017). But very limited migration studies have been investigated based on other biopolymers like PVA and ST for potential material packaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of such release provides critical information for environmental nanoobject exposure from biodegradable nanocomposites. In our previous studies [19][20][21], we have investigated the release of GNP and MWCNTs from the composite film GNP/MWCNT/PLA in alcoholic and acid food simulants, high temperature migration conditions, such as: (i) strong static migration test (with heating at 90 o C for 4 hours); and (ii) ultra-strong dynamic migration test (heating at 90 o C for 4 hours followed by subsequent storage for 10 days at 40°C, including dynamic treatment for 1 min daily). The strong static and ultra-strong dynamic migration conditions were set accordingly with the prescription in EU Regulation 10/2011 (EU 2011) [28] and literature sources [29,30] for migration of polymer films in food simulants.…”
Section: Release Of Graphene and Carbon Nanotubes Due To Degradation mentioning
confidence: 88%
“…At the strong static migration test [19,20], we have observed that large graphene nanoplatelets (GNP) of about 100-1000 nm in length and a few nanometers in thickness indeed migrate from the poly(lactic) composite film, GNP/MWCNT/PLA, into food simulants. We have assumed that heating above the glass transition temperature enhance the dynamics of polymer molecules and facilitate the diffusion of graphene nanoplatelets from PLA film into food simulant.…”
Section: Release Of Graphene and Carbon Nanotubes Due To Degradation mentioning
confidence: 99%
See 1 more Smart Citation